Development of Teaching Materials on Islam and Human Rights Based on Religious Moderation in the Islamic Family Law Study Program - Saputera, Abdur Rahman Adi; Iman, Muhammad Nur; Aning, Wardhani Djenaan (At-Tafkir, 2024)
This study aims to develop valid, practical, and effective teaching materials on Islam, Human Rights (HR), and religious moderation relevant to the Islamic Family Law Study Program (HKI) at IAIN Sultan Amai Gorontalo. The urgency of developing this material lies in the need to enhance students' understanding of HR principles and religious moderation within the context of Islamic family law, which is essential to shaping a more inclusive and tolerant legal perspective. Given the strategic role of the HKI program in Islamic legal education, the development of these teaching materials is expected to enrich existing course content and address the educational challenges in the global era, which increasingly emphasizes HR values. The research method used in this study is research and development (R&D) with the Borg & Gall model, chosen for its comprehensive approach in developing educational products, from needs identification, material design, product testing, revisions, to dissemination of the final product. This process aims to produce teaching materials that align with the HKI curriculum requirements and are well accepted by students. The research results indicate that the developed teaching materials received positive feedback with an average score of 3.46, indicating very good quality. The impact of these results shows that the new teaching materials can improve students' understanding of HR issues and religious moderation, while enriching their perspective on Islamic family law in a more progressive way. However, several factors hinder the implementation of these materials, such as the lack of understanding among lecturers about religious moderation, limited references, and insufficient training for instructors. Therefore, further institutional support is needed to facilitate the effective use of these materials in the HKI program’s learning process, thus contributing to improving the quality of Islamic family law education in the future.